Analisis Inovasi Usaha pada UMKM Coffee Shop di Kecamatan Coblong Kota Bandung - Trustorini Handayani; Nando Tifano; Trenggono Tri Widodo (Jurnal Riset dan Inovasi Manajemen, 2025)
The main objective of this study is to analyze business innovation implemented by Coffee Shops in Coblong District, Bandung City, considering the increasing number of similar businesses emerging, triggering fierce competition in this industry. In facing these conditions, business actors are required to continue to innovate to be able to survive and excel in the competition. This study uses a descriptive analysis method with an approach to calculating the average value of each variable measured using a Likert scale. The study population consisted of 38 Coffee Shop entrepreneurs who served as research samples. Based on the analysis results, business innovation was measured through four main indicators, namely relative advantage, compatibility, dissemination, and communicability. In general, Coffee Shops in this area have succeeded in innovating well, although there are variations in achievement for each indicator. The indicator with the highest score is communicability, which refers to the ability of staff, especially baristas and cashiers, to interact with customers in a friendly, polite, and effective manner. This is not only limited to greeting but also creating a comfortable atmosphere so that customers feel appreciated, which ultimately increases customer loyalty. Conversely, the indicator with the lowest score is dissemination, which indicates that most customers tend to only order a specific type of coffee without exploring other menu variations. This condition can be seen as an opportunity to strengthen superior products, but also signals that the product diversification strategy is not running optimally. Therefore, it is important for coffee shop businesses in Coblong to develop a menu diversification strategy, both in terms of beverage types and service variations, so that the business remains competitive, relevant to diverse consumer preferences, and able to increase competitiveness amidst the increasingly rapid growth of the coffee shop industry.